PDGFRα-Signaling Is Dispensable for the Development of the Sinoatrial Node After Its Fate Commitment - Zheng, Xi; Wang, Fengjiao; Hu, Xiaoxiao; Li, Hua; Guan, Zhen; Zhang, Yanding; Hu, Xuefeng (Frontiers in Cell and Developmental Biology, 2021)
Palate-derived growth factor receptor α (Pdgfrα) signaling has been reported to play important roles in the cardiac development. A previous study utilizing Pdgfrα conventional knockout mice reported hypoplasia of the sinus venous myocardium including the sinoatrial node (SAN) accompanied by increased expression of Nkx2.5. This mouse line embryos die by E11.5 due to embryonic lethality, rendering them difficult to investigate the details. To elucidate the underlying mechanism, in this study, we revisited this observation by generation of specific ablation of Pdgfrα in the SAN by Shox2-Cre at E9.5, using a Shox2-Cre;Pdgfrαflox/flox conditional mouse line. Surprisingly, we found that resultant homozygous mutant mice did not exhibit any malformation in SAN morphology as compared to their wild-type littermates. Further analysis revealed the normal cardiac function in adult mutant mice assessed by the record of heart rate and electrocardiogram and unaltered expression of Nkx2.5 in the E13.5 SAN of Pdgfrα conditional knockout mice. Our results unambiguously demonstrate that Pdgfrα is dispensable for SAN development after its fate commitment in mice.